2019
DOI: 10.3389/fncel.2019.00472
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Morphometric Parameters Correlate With the Expression Level of IL-1β, and Allow Identifying Different Activated Morphotypes

Abstract: Microglia are the resident macrophages in the brain. Traditionally, two forms of microglia have been described: one considered as a resting/surveillant state in which cells have a highly branched morphology, and another considered as an activated state in which they acquire a de-ramified or amoeboid form. However, many studies describe intermediate microglial morphologies which emerge during pathological processes. Since microglial form and function are closely related, it is of interest to correlate microglia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 59 publications
5
106
0
Order By: Relevance
“…1, C to F). These projections are known to be responsible for increasing microglial cell surface area within the brain microenvironment as a result of microglial activation and are typically found at the tips of microglial processes (28,29). Conversely, we observe that (GT)6-SWCNT exposure promoted growth of projections along the entire length of the cell branches, not only at the tip of microglial processes (Fig.…”
Section: Morphological Response Of Sim-a9 Microglia To Swcntsmentioning
confidence: 65%
“…1, C to F). These projections are known to be responsible for increasing microglial cell surface area within the brain microenvironment as a result of microglial activation and are typically found at the tips of microglial processes (28,29). Conversely, we observe that (GT)6-SWCNT exposure promoted growth of projections along the entire length of the cell branches, not only at the tip of microglial processes (Fig.…”
Section: Morphological Response Of Sim-a9 Microglia To Swcntsmentioning
confidence: 65%
“…Our results showed that microglia in ischemic penumbra regions was signi cantly activated, showing a rod-shaped morphology with a large cell body [44] . In comparison, GSS treatment signi cantly inhibited the activation of microglia in ischemic penumbra regions where most microglia were rami ed shape as showing in sham rats [45,46] .…”
Section: Discussionmentioning
confidence: 85%
“…The increased microglial solidity may represent a change in the distribution of the arborization, particularly a decreased distance between branches which would reflect a more convex-like shape. Others also hypothesized that an increase of the solidity value occurs during the morphological shift from a ramified to an amoeboid shape upon neuroinflammatory insults and represents a de-ramified or bushy morphology [103,104], a phenotype seen upon exposure to stress [105]. In a bacterial MIA mouse model, microglia were previously shown to shift their morphology to an ameboid shape in adolescent (PND40) offspring amygdala [106].…”
Section: Discussionmentioning
confidence: 99%